The Expression of the Psychological Chronotope Through the Concept of Kòz in "Lives in The Dream" - Shodmonova Mahzuma Jumanazarovna (Scientific Trends, 2025)
This article analyzes how the diagnosis of chronotope is expressed through the concept of the “eye” in Abdullah Qahhor's “life at noon”. The connection and text of the artistic psyche with space, the inner evenings of the hero are illuminated through the eye twine.
Keywords: Space and time problem, chronotope, psychological chronotope, eye concept.